Theta Oscillations at Subthalamic Region Predicts Hypomania State After Deep Brain Stimulation in Parkinson's Disease - Chen, Yi-Chieh; Wu, Hau-Tieng; Tu, Po-Hsun; Yeh, Chih-Hua; Liu, Tzu-Chi; Yeap, Mun-Chun; Chao, Yi-Ping; Chen, Po-Lin; Lu, Chin-Song; Chen, Chiung-Chu (Frontiers in Human Neuroscience, 2021)
Subthalamic nucleus (STN) deep brain stimulation (DBS) is an effective treatment for the motor impairments of patients with advanced Parkinson’s disease. However, mood or behavioral changes, such as mania, hypomania, and impulsive disorders can occur post-operatively. It has been suggested that these symptoms are associated with the stimulation of the limbic subregion of the STN. Electrophysiological studies demonstrate that the low frequency activities in ventral STN are modulated during emotional processing. Here we report twenty-two patients with Parkinson’s disease who underwent STN DBS for treatment of motor impairment and presented stimulation-induced mood elevation during initial postoperative programming. The contact at which a euphoric state was elicited by stimulation was termed the hypomania-inducing contact (HIC) and was further correlated with intraoperative local field potential recorded during the descending of DBS electrodes. The power of four frequency bands, θ (4-7 Hz), α (7-10 Hz), β (13-35 Hz) and γ (40-60 Hz), were determined by a nonlinear variation of spectrogram, the concentration of frequency of time (conceFT). The depth of maximum θ power is located approximately 2mm below HIC on average and has significant correlation with the location of contacts (r=0.676, p<0.001), even after partializing the effect of α and β, respectively (r=0.474, p=0.022; r=0.461, p=0.027). The occurrence of HIC was not associated with patient-specific characteristics such as age, gender, disease duration, motor or non-motor symptoms before operation or improvement after stimulation. Taken together, these data suggest that the location of maximum θ power is associated with the stimulation induced hypomania and the prediction of θ power is frequency specific. Our results provide further information to refine targeting intraoperatively and select stimulation contacts in programming.